The relationship between organisational modal personality, organisational commitment and intention to turnover. - Siemers, Ian (My University, 2010)
The aim of this research is explore the possible relationship between personality and turnover. This relationship is framed within the Attraction-Selection-Attrition (ASA) Model, a model that describes the process through which homogeneity of personality types within organisations occurs. Following a review of literature relevant to the topic, it is suggested that failure to fall with the majority personality cluster, should be related to low levels of organisational commitment and high levels of intention to turnover. Both of these variables are viewed as indicators of one’s turnover likelihood. In testing this relationship, the research further aims to provide empirical evidence for the notion of Attrition, an otherwise absent feature of ASA research. The study involved the participation of 101 employees from a Johannesburg based organisation. Each respondent was presented with the Work Personality Index (WPI), the Organisational Commitment Questionnaire (OCQ) and the Intention to Turnover Scale (ITS). The WPI results were analysed with the use of cluster analysis. The organisational commitment and intention to turnover scores of the resultant personality clusters were then analysed to determine whether or not differences existed between these clusters. The research failed to provide outright evidence for the predicted relationship between personality cluster membership and turnover. There was some evidence for the notion of Attrition, yet the nature of that attrition was shown to be different from the expected form under the ASA model. The research showed that it is possible that complementary and supplementary fit (mechanisms that are related to Attrition, and thus turnover) are both present within the sample, suggesting that ASA model requires some revision. Limitations, as well as theoretical and practical implications, of this study are too considered. Finally the study suggests further possible lines of research that could shed light on the relationship between personality and organisational behaviours, of which turnover is one of many.